Pulmonary Inflammatory Rhabdomyoblastic Tumor: Case Report - Barros, Pedro Pinheiro (2023)
Introduction: Primary lung sarcomas are rare malignant tumors with an estimated incidence of around 0.5% of all lung neoplasms. Of their typifications described in the literature, two especially, leiomyosarcomas and rhabdomyosarcomas, have similarities in their genetic, morphological and immunohistochemical profile, which led them to be classified with the same name: inflammatory rhabdomyoblastic tumor. This type of tumor usually affects soft tissues in the extremities and trunk, and predominates among young and middle-aged men. Due to the small number of cases of rhabdomyoblastic tumors reported in the literature, both their diagnosis and treatment are poorly described. Case report: Female patient, 19 years old, who had three episodes of respiratory infection in the lower lobe of the right lung in a period of 18 months. Computed tomography of the chest showed obstruction of the intermediate bronchus and areas of bronchiectasis in the right lower lobe. In view of this, a lower middle bilobectomy was performed through robotic surgery. The patient was discharged from hospital three days after the operation. Immunohistochemistry revealed low-grade inflammatory rhabdomyoblastic tumor. Conclusion: This report described a case of a rare lung tumor, submitted to a surgical technique not yet reported for this type of pathology.